2021
DOI: 10.1101/2021.09.15.460381
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SLC25A39 is necessary for mitochondrial glutathione import in mammalian cells

Abstract: Glutathione (GSH) is a small molecule thiol abundantly present in all eukaryotes with key roles in oxidative metabolism. Mitochondria, as the major site of oxidative reactions, must maintain sufficient levels of GSH to perform protective and biosynthetic functions. GSH is exclusively synthesized in the cytosol, yet the molecular machinery involved in mitochondrial GSH import remain elusive. Here, using organellar proteomics and metabolomics approaches, we identify SLC25A39, a mitochondrial membrane carrier of … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 49 publications
1
20
0
Order By: Relevance
“…Our work shows that A39 is required for GSH transport, and the screen further suggests that the impact of impaired mitochondrial GSH transport is sensitive to genetic and environmental states, notably iron metabolism. While this manuscript was in revision, Wang et al manuscript in Biorxiv 66 independently reported the characterization of SLC25A39 as a mitochondrial GSH transporter and a secondary defect of iron-sulfur cluster deficiency in cells depleted of mitochondrial glutathione. This observation might explain the decreased mitochondrial respiration in the A39 KO cells we have observed and the buffering interaction with the iron transporter SLC25A37 in our screen.…”
Section: Discussionmentioning
confidence: 99%
“…Our work shows that A39 is required for GSH transport, and the screen further suggests that the impact of impaired mitochondrial GSH transport is sensitive to genetic and environmental states, notably iron metabolism. While this manuscript was in revision, Wang et al manuscript in Biorxiv 66 independently reported the characterization of SLC25A39 as a mitochondrial GSH transporter and a secondary defect of iron-sulfur cluster deficiency in cells depleted of mitochondrial glutathione. This observation might explain the decreased mitochondrial respiration in the A39 KO cells we have observed and the buffering interaction with the iron transporter SLC25A37 in our screen.…”
Section: Discussionmentioning
confidence: 99%
“…Cysteine is rate-limiting for production of glutathione (GSH), a prominent antioxidant in mammalian cells [1,6,7]. Mitochondrial GSH import is essential for the activity of FeS cluster proteins and mitochondrial mRNA translation [8]. GSH dysregulation contributes to many pathological conditions including neurodegenerative disorders, anemia, aberrant aging, and cancer initiation and progression [7,8].…”
Section: Cellular Functions Of Cysteine and Its Crucial Role In Cancermentioning
confidence: 99%
“…Therefore, ROS and lipid peroxidation products will probably perturb glutathionylation of these proteins, leading to loss of mitochondrial regulation. Furthermore, GSH in mitochondria is derived from the cytoplasmic pool by the actions of solute carrier (SLC) 25A39 and SLC25A40 [124], which indicates it is vulnerable to oxidative stress in other subcellular compartments. Interestingly, depletion of GSH is necessary for the biogenesis of iron-sulfur cluster proteins within the mitochondrion, such as succinate dehydrogenase, cytochrome c oxidase subunit II, NADH dehydrogenase [ubiquinone] 1 beta subcomplex subunit 8 and mitochondrial rRNA methyltransferase 1 [124].…”
Section: Mitochondrial Dysfunction Excess Generation Of Ros and Nashmentioning
confidence: 99%
“…Furthermore, GSH in mitochondria is derived from the cytoplasmic pool by the actions of solute carrier (SLC) 25A39 and SLC25A40 [124], which indicates it is vulnerable to oxidative stress in other subcellular compartments. Interestingly, depletion of GSH is necessary for the biogenesis of iron-sulfur cluster proteins within the mitochondrion, such as succinate dehydrogenase, cytochrome c oxidase subunit II, NADH dehydrogenase [ubiquinone] 1 beta subcomplex subunit 8 and mitochondrial rRNA methyltransferase 1 [124]. In this context it is notable that cholesterol enriched mitochondria exhibit diminished membrane fluidity and GSH transport (presumably via SLC25A39 and SLC25A40) that is likely to impair their function [125].…”
Section: Mitochondrial Dysfunction Excess Generation Of Ros and Nashmentioning
confidence: 99%
See 1 more Smart Citation